Three Patients of the Early Onset Epileptic Spasms without Hypsarrhythmia - Ohshiro, Ikko; Okanishi, Tohru; Ohta, Ryo; Ohta, Kento; Arai, Yuto; Kanai, Sotaro; Fujimoto, Ayataka; Maegaki, Yoshihiro (Neuropediatrics, 2024)
Epileptic spasms without hypsarrhythmia occur when patients do not display hypsarrhythmia on electroencephalogram (EEG) at the onset and throughout the clinical course. We report three patients of epileptic spasms in patients with early onset, all of whom experienced other types of seizures.We detail three patients (two boys and one girl) of epileptic spasms without hypsarrhythmia, occurring between 1 and 3 months of age, with no abnormalities detected on neurometabolic analysis and brain magnetic resonance imaging. Long-term video-EEG monitoring revealed epileptic spasms with focal onset seizures in two patients, and epileptic spasms followed by generalized tonic-clonic seizures in one patient. Hypsarrhythmia was never observed in repeated EEG examinations. Two patients achieved seizure freedom and improved development through treatment with topiramate alone or in combination with valproate, without requiring hormonal therapies or vigabatrin. The remaining patient achieved seizure freedom following administration of antiseizure medications, including topiramate, after a trial of adrenocorticotropic hormone therapy.We report the cases of three patients with early onset epileptic spasms without hypsarrhythmia. All patients achieved seizure freedom after topiramate treatment. Topiramate may be considered as a relatively effective antiseizure medication for early onset epileptic spasms without hypsarrhythmia.
Keywords: epileptic spasms without hypsarrhythmia; early onset; topiramate; focal onset seizure